2006
DOI: 10.3390/mca11020151
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Active and Passive Vibration Control of Non-Linear Simple Pendulum. Part II: Longitudinal Tuned Absorber and Negative Gφ and Gφn Feedback

Abstract: In part I [1] we dealt with a tuned absorber, which can move in the transversally direction, where it is added to an externally excited pendulum. Active control is applied to the system via negative velocity feedback or its square or cubic value. The multiple time scale perturbation technique is applied throughout. An approximate solution is derived up to second order approximation. The stability of the system is investigated applying both frequency response equations and phase plane methods. The effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…represents the complex conjugate of the previous terms. Substituting (12) into (10) and using the response condition equation (4) leads to secular terms. Eliminating these secular terms leads to solvability for the first-order approximation:…”
Section: Mathematical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…represents the complex conjugate of the previous terms. Substituting (12) into (10) and using the response condition equation (4) leads to secular terms. Eliminating these secular terms leads to solvability for the first-order approximation:…”
Section: Mathematical Analysismentioning
confidence: 99%
“…Eissa [9] reported that one of the most effective tools for the control of passive vibration is the dynamic absorber or the damper or the neutralizer. Vibration and dynamic chaos of both simple pendulum and spring pendulum that represent ship's roll motion have been studied by Eissa and Sayed [10][11][12][13][14]. The effects of the transverse and longitudinal tuned absorbers on the vibrations of both systems under single harmonic excitation have been studied numerically to control the oscillations of both systems.…”
Section: Introductionmentioning
confidence: 99%
“…Eissa and Sayed [10,11] made a comparison between the active and the passive vibration control of a simple pendulum described by a second order nonlinear differential equation having both quadratic and cubic nonlinearities. They controlled the system applying either nonlinear absorber (passive control) or negative velocity feedback or its square or cubic value (active control).…”
Section: Introductionmentioning
confidence: 99%
“…They applied saturation values of different parameters as optimum working conditions for vibration suppression of the cantilever. Eissa et al [16,17] presented tuned absorbers in both transverse and longitudinal directions of a simple pendulum which was designed to control one frequency at primary resonance. They demonstrated the effectiveness of the absorber for passive control.…”
Section: Introductionmentioning
confidence: 99%